The Future in Anthropocene Science - P. W. Keys; L. Badia; R. Warrier (Earth's Future, 2024)
Abstract The Anthropocene is the present time of human‐caused accelerating global change, and new forms of Anthropocene risk are emerging that society has hitherto never experienced. Science and policy are grappling with the temporal and spatial magnitude of these changes. However, there is a gap in the transparency—and perhaps even in the awareness—of the profound role that Anthropocene science plays in shaping the structure and possibility of our future world. In this work, we explore three key features of Anthropocene scenarios, including: worlding capacity, values shaping what is possible, and refusal to look. We explore these three features using three cases of Anthropocene science including international energy scenarios, climate change projections, and the possibility of social collapse. We discuss how Anthropocene science modulates new risks and systematically, though perhaps inadvertently, entrains certain social‐ecological futures. We find that clarity in these three attributes of Anthropocene science could enhance its integrity and build trust, not least in the arena of public policy. We conclude with recommendations for improving the interpretability and scope of Anthropocene science in the context of a growing urgency for accurate information to inform our collective future.